Hyperglycaemia and Ischaemia Impair Wound Healing via Toll-like Receptor 4 Pathway Activation in vitro and in an Experimental Murine Model. (January 2020) - Portou, Mark J.; Yu, Rebekah; Baker, Daryll; Xu, Shiwen; Abraham, David; Tsui, Janice
Abstract : Objective: Diabetes mellitus has reached epidemic proportions. Foot ulceration is a multifactorial complication of diabetes associated with marked morbidity and mortality. Innate immune Toll-like receptor 4 (TLR4) mediated inflammation has been implicated in the systemic pathogenesis of diabetes and may contribute to impairment of wound healing. This study investigates the effect of high glucose and hypoxic conditions on TLR4 activation and signalling in vitro and in vivo . Methods: Fibroblasts cultured at physiological glucose concentration (5.5 mM) were exposed to glucose concentrations from 0 mM to 25 mM, with duplicates placed in a hypoxic chamber. TLR4 inhibition was assessed in the 25 mM glucose groups. Diabetes was induced in wild type (WT) and TLR4 knockout (KO) C57BL/6 mice by intraperitoneal injection of low dose streptozocin (STZ). Hindlimb ischaemia was induced by femoral artery ligation four weeks post streptozocin, and a full thickness 4 mm skin wound inflicted below the knee. Wound healing was assessed via digital planimetry on days 3, 7, and 14 post surgery. Results: Hypoxic and high glucose (25 mM) conditions led to an increase in TLR4 protein expression, apoptosis, and interleukin (IL)-6 release. Inhibition with a TLR4 neutralising antibody and specific TLR4 antagonist ameliorated the effects of high glucose and ischaemia ( p < .05). In vivo, wound healing was significantly impaired in the diabetic ischaemic group at day 14 ( p < .05). Diabetic ischaemic wounds in TLR4 KO mice exhibited significantly improved healing rates compared with those in WT mice at all time points. Conclusion: Hypoxia stimulates upregulation of TLR4 protein expression and this effect is exaggerated by hyperglycaemia. In TLR4 KO mice, there is a significant improvement in the healing of diabetic ischaemic wounds compared with WT. It is suggested that a synergistic effect between hypoxia and hyperglycaemia impairing wound healing exists, through TLR4 mediated inflammation.